Manual de avaliação da aprendizagem no curso de graduação em Odontologia da Unifenas – Câmpus de Varginha - MG - MIRANDA, J. R. (2018)
In contemporary education, assessment is no longer just an instrument to quantify content apprehension by the student and has become an important component of the teaching-learning process. Assessment should fit the domains of knowledge: cognitive, psychomotor and affective, which requires different types of instruments. The objective of this work was to elaborate a manual fordentistry students assessment, to present to teachers instruments that can be used in different domains at the dentistry course of Universidade José do Rosário Vellano - UNIFENAS - Campus de Varginha. This manual presents the definition, indication and operational aspects of five evaluation instruments: portfolio, multiple choice questions, discursive questions, mini-clinical evaluation exercise and objective structured clinical examination.